2022
DOI: 10.1038/s41598-022-13568-5
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional warming over the Barents area

Abstract: In recent decades, surface air temperature (SAT) data from Global reanalyses points to maximum warming over the northern Barents area. However, a scarcity of observations hampers the confidence of reanalyses in this Arctic hotspot region. Here, we study the warming over the past 20–40 years based on new available SAT observations and a quality controlled comprehensive SAT dataset from the northern archipelagos in the Barents Sea. We identify a statistically significant record-high annual warming of up to 2.7 °… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(117 citation statements)
references
References 58 publications
2
64
0
Order By: Relevance
“…The most extreme AA values occur in the sea areas near Novaya Zemlya, which were locally warming up to seven times as fast as the global average. These high warming rates are consistent with recent research 44 , and evidently, the primary reason for such a high amplification ratio is the reduction of cold-season ice cover, which has been most pronounced in the Barents Sea 44,45 . Furthermore, it has been found that changes in atmospheric circulation have amplified the warming in this area 46,47 .…”
Section: Observedsupporting
confidence: 91%
“…The most extreme AA values occur in the sea areas near Novaya Zemlya, which were locally warming up to seven times as fast as the global average. These high warming rates are consistent with recent research 44 , and evidently, the primary reason for such a high amplification ratio is the reduction of cold-season ice cover, which has been most pronounced in the Barents Sea 44,45 . Furthermore, it has been found that changes in atmospheric circulation have amplified the warming in this area 46,47 .…”
Section: Observedsupporting
confidence: 91%
“…However, there is considerable regional variability in the magnitude of this warming, mainly related to differences in the proximity of permafrost temperatures to 0 • C [7] and differences in climate setting. The greatest changes are observed at permafrost stations on Svalbard, which are located in a region that currently warms up until seven times faster than the global average [38].…”
Section: Discussionmentioning
confidence: 99%
“…Such a coordinated effort on long-term effects is required to gain a holistic understanding of future changes in the tundra biome and its possible resistance and resilience to both winter and summer warming (Bjorkman et al, 2020). This is especially urgent given that winter warming is by far outpacing summer warming (Isaksen et al, 2022b), with potentially ecosystem-wide consequences such as alteration of below-ground vegetation productivity, microorganism activity, and carbon flux exchange, and cascading effects across the food web. This pioneer long-term icing experiment sets the stage for forthcoming studies to fill this fundamental knowledge gap.…”
Section: Discussionmentioning
confidence: 99%
“…The high Arctic Svalbard (78°17’N, 16°02’E) is a region warming twice faster than the Arctic average and five-seven times faster than the global average (Isaksen et al 2022b). The experiment was located in the valley of Adventdalen and lasted for five consecutive years (January 2016–August 2020).…”
Section: Methodsmentioning
confidence: 99%